Gambaran Pola Konsumsi Minuman Berenergi, Kopi, serta Kebiasaan Merokok pada Sopir Angkot di Terminal Ciamis - Yeni Sumartini; Mutia Hadi Pratiwi; Alzena Kevina Shahla; Natasya Hairunnisa; Devina Tiara Safitri; Siti Faridah Sathiah N. A (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The drivers of public transportation have long working hours that demand high levels of alertness, which leads many of them to rely on energy drinks, coffee, and smoking as coping mechanisms. This study aims to describe the consumption patterns of energy drinks, coffee, and smoking habits among public transportation drivers at Ciamis Terminal. The research was conducted descriptively with a cross-sectional approach on 44 drivers selected through accidental sampling. Data were collected using a questionnaire and analyzed using univariate analysis. The results indicate that the majority of respondents were active smokers (84.1%) and consumed coffee regularly (75%), mostly instant coffee. In contrast, the consumption of energy drinks was relatively low (13.6%). These findings suggest that these three habits have become an integral part of the daily routine of public transportation drivers.